Rhizobium Symbiotic Capacity Shapes Root-Associated Microbiomes in Soybean - Liu, Yuanhui; Ma, Bin; Chen, Wenfeng; Schlaeppi, Klaus; Erb, Matthias; Stirling, Erinne; Hu, Lingfei; Wang, Entao; Zhang, Yunzeng; Zhao, Kankan; Lu, Zhijiang; Ye, Shudi; et al. (Frontiers in Microbiology, 2021)
Root-microbiome interactions are of central importance for plant performance and yield. A distinctive feature of legumes is that they engage in symbiosis with rhizobia. If and how the rhizobial symbiotic capacity modulates root-associated microbiomes are not well understood. We determined root-associated microbiomes of soybean inoculated with wild type (WT) or a noeI mutant of Bradyrhizobium diazoefficiens by amplicon sequencing. UPLC-MS/MS was used to analyze root exudates. noeI gene is responsible for the methylation of signal molecular secreted by rhizobia. Soybean plants inoculated with noeI mutant showed a significant decrease in nodulation and root-flavonoid exudation compared to plants inoculated with WT rhizobia. noeI mutant-inoculated roots exhibited strong changes in microbiome assembly in the rhizosphere and rhizoplane, included reduced diversity, co-occurrence interactions and a substantial depletion of beneficial microbes on the roots. The flavonoid supplementation restored 37.5% of families significantly enriched in nodules inoculated with WT rhizobia. The functional profile of OTUs significantly enriched in soils treated with flavonoid and in nodules inoculated with WT rhizobia were mainly related to metabolic pathways. These results illustrate that rhizobial symbiotic capacity dramatically alters root-associated microbiomes, most likely by changing root exudation patterns. This study has important implications for understanding the evolution of plant-microbiome interactions.